Butterfly community (Lepidoptera) at Joben Tourism Park (Joben Eco Park) Regency of East Lombok - Rahmatul Aulani Yuniartin; Mohammad Liwa Ilhamdi; Gito Hadiprayitno (Jurnal Pijar Mipa, 2023)
Joben Eco Park is located in the ​​Joben Resort area, Mount Rinjani National Park Center Pesanggarahan Village, Montong Gading Subdistrict, East Lombok Regency. This research is an exploratory, descriptive study that aims to discover the butterfly community in Joben Eco Park, East Lombok Regency. Data collection used a purposive survey method whit a sweeping technique following two predetermined observation lines. The research results were obtained from 375 individual butterflies covering 29 species, with 11 genera and 4 families. Analysis of the butterfly diversity index using the Shannon-Winner formula obtained a butterfly species diversity index value in Joben Eco Park in general of 3.033, which falls into the high category. Analysis of the dominance index using a formula from Simpson obtained a value of 0.06.